2023
DOI: 10.1126/sciadv.abn5429
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of distinct vertebrate gastrulation modes via modulation of key cell behaviors in the chick embryo

Abstract: The morphology of gastrulation driving the internalization of the mesoderm and endoderm differs markedly among vertebrate species. It ranges from involution of epithelial sheets of cells through a circular blastopore in amphibians to ingression of mesenchymal cells through a primitive streak in amniotes. By targeting signaling pathways controlling critical cell behaviors in the chick embryo, we generated crescent- and ring-shaped mesendoderm territories in which cells can or cannot ingress. These alterations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 62 publications
6
22
0
Order By: Relevance
“…This sickle-shaped mesendoderm precursor region contracts along its long axis towards the AP midline of the embryo and extends along this midline in anterior direction to form the primitive streak. Measurements of the directions of intercalations show that they are aligned along the long axis of the mesendoderm sickle in the direction of the contraction of the sickle and correlate well with the direction and magnitude of the anisotropic strain rate component ( Rozbicki et al, 2015 ; Chuai et al, 2023 ). These directed intercalations are mediated by super cellular myosin cables in aligned junctions in the direction of intercalation ( Rozbicki et al, 2015 ; Saadaoui et al, 2020 ; Serrano Nájera and Weijer, 2020 ).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…This sickle-shaped mesendoderm precursor region contracts along its long axis towards the AP midline of the embryo and extends along this midline in anterior direction to form the primitive streak. Measurements of the directions of intercalations show that they are aligned along the long axis of the mesendoderm sickle in the direction of the contraction of the sickle and correlate well with the direction and magnitude of the anisotropic strain rate component ( Rozbicki et al, 2015 ; Chuai et al, 2023 ). These directed intercalations are mediated by super cellular myosin cables in aligned junctions in the direction of intercalation ( Rozbicki et al, 2015 ; Saadaoui et al, 2020 ; Serrano Nájera and Weijer, 2020 ).…”
Section: Introductionmentioning
confidence: 77%
“…Previous experiments have shown that the embryo scale tissue flows driving the lateral to medial convergence and posterior anterior extension of the posterior sickle-shaped mesendoderm precursor domain that results in its transformation into the streak is driven by directed cell intercalations. These cells undergoing directed intercalations are characterised by an anisotropic cell shape and an anisotropic distribution of active myosin II in their cell junctions, organised in supercellular chains of variable length ( Figure 8A and A’ ; Rozbicki et al, 2015 ; Chuai et al, 2023 ). We here make a qualitative comparison of the myosin-driven intercalations in the model with the myosin-dependent directed cell intercalations driving tissue deformations in the sickle-shaped mesendoderm precursor region of the early gastrulation stage chick embryo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S10 shows the same measured pMLC signal intensity as a scalar field over the embryo, demonstrating an overall increase in myosin activity. For experimental details, see ( 4 ). ( F ) Here, we construct a theoretical framework coupling velocity, actomyosin orientation, and intensity that explains observed gastrulation flows in recent experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The pMLC anisotropy is quantified from the asymmetry of the Fourier power spectrum ( 11 ), calculated in a tiling pattern over the embryo, while myosin intensity is calculated as average intensity in the same tiles. For experimental details, see the recently published paper ( 4 ). The panels show a high increase of active myosin over time (see also fig.…”
Section: Introductionmentioning
confidence: 99%